Administrasi Kesiswaan Digital Dalam Bingkai Sistem Informasi Manajemen Berbasis Nilai Peradaban Islam - Aisyah Shinta Balqis (Jurnal Adab dan Peradaban Islam, 2026)
This article examines the effectiveness of the Educational Management Information System (EMIS) in the digitalization of student administration, analyzed through the lens of Islamic adab (ethics of knowledge) and Islamic civilization. The rich Islamic scholarly tradition — as exemplified by bayt al-hikmah, madrasah, and ribath institutions — places administrative precision, data integrity, and amanah (trustworthiness) in knowledge management as core civilizational values. This mixed-method study involved 120 respondents from 6 Islamic senior high schools in Lampung Province. Results show that EMIS implementation increased student administrative efficiency by 72%, reduced data errors by 65%, and improved user satisfaction by 78%. The study argues that digitalization of student administration is not merely a technical modernization but a manifestation of Islamic adab values — amanah (trustworthiness), itqan (excellence in work), and khidmah al-‘ilm (service to knowledge) — consonant with the Islamic civilizational mission of orderly and equitable knowledge transmission. This research contributes to the discourse on social transformation of Islamic educational institutions in responding to modernity while preserving civilizational roots.